Berdamai dengan Luka Masa Lalu: Studi Fenomenologi tentang Makna Self-acceptance pada Perempuan Korban KDRT - Dien Amrina Rasyada; Mimbar Oktaviana (Jurnal Ragam Pengabdian, 2026)
This study aims to understand the self-acceptance process among domestic violence survivors. A qualitative method with a phenomenological approach was employed to in-depth explore the meaning of the participants’ lived experiences. Purposive sampling and face-to-face interviews were used to select and collect data. The findings revealed three main themes: (1) internal dynamics and emotional regulation, (2) self-agency reclamation through empowerment and social support, and (3) self-transformation toward self-acceptance and personal growth. These findings are expected to contribute to the development of trauma-sensitive psychological interventions, particularly for survivors of domestic violence